Masquerade Performance Tradition of Idoma: Issues of Limitation and Methodological Approaches in Research (Global Journal of Human-Social Science, 2015)
This work presents the researcher's experience of a field work on Idoma masquerade tradition. This paper examines the probable difficulties as well as procedures of data collection in masquerade studies. The work states that masquerade performance is the cradle of Idoma civilization. This validates the important place of systemic methodological strategies in researches of this nature. The research shows that Idoma masquerades are conceived as spiritual contraptions which are personified in bodily forms. These play functional roles in the peoples' lives. As a result they are guarded jealously. Findings show that people's understanding of the world around them is sustained by the peculiarities of their cultures and traditions. The paper concludes that tools like oral interviews, participation observation, case studies, holism and behind the scene involvement are important instruments in conducting successful researches in Idoma masquerades. Thus presents that using the qualitative approach to methodology achieves better outcomes.
Keywords: masquerade; spirits; performance; idoma; worldview; methodology; tools; research; function; procedures